The Impact of Culture and Society on Crisis Perception, Management, and Learning in the Indian context - Mrudula Anne; Jia Wang; Deborah Chang (Adult Education Research Conference, 2013)
It was tough going through so many failures that time. I realized most of the things I was after are not going to come to me. So, as a punishment, I did one year long-term and gave the EAMCET exam. During this one year, I learnt a lot about life, the importance of planning ahead and putting the hard work. It changed the way I approached life. It made me realize that nothing in this world comes to you unless you work towards it